Pengaruh IPM, Pengangguran, Dan Kemiskinan Terhadap Pertumbuhan Ekonomi Di Kabupaten Malang - Bimbi Resti Mataheurilla; Lucky Rachmawati (Universitas Negeri Surabaya, 2021)
Abstract This study aims to see the influence of the independent variable Human Development Index, Unemployment and Poverty on the dependent variable Economic Growth in the Malang Regency area. This study uses Time Series data for the period 2010 - 2020. The calculation of multiple linear regression shows that HDI has a significant negative effect on Economic Growth, Unemployment has no visible effect on Economic Growth and Poverty has no visible effect on Economic Growth. As for the independent variables HDI, Unemployment and Poverty, it can be seen that there is a simultaneous and relevant influence on Economic Growth in Malang Regency in 2010 - 2020. Keywords: HDI, Unemployment, Poverty, Economic Growth